Urban growth in Sudan - Babiker, Insaf Ali Omar (Journal of Humanities & Social Sciences, 2022)
The beginning of the third millennium have carried out global geographical changes from all walks of life, and the rapid development has become a feature of this era, accordingly the decision-makers at all levels are closely following the local and global developments and changes. The conference’s topics gains an international fame as it is the geography point of view, as well as the use of its applications in realizing much of the conference’s objectives. We expect from the conference to address the roll of geography in the development, and support the group and cognitive contact among geographers and others from different parts of countries. The study used the geographical approach in processing the studied phenomenon, and the spatial analysis approach, in addition to the analysis of the civilization factors. We must point out here that the population study is necessarily, based on limited numbers and statistical data, and Sudan is one of the countries in which data and statistical numbers are provided. After mentioning the regional and urban planning concepts, the paper has focused on the urban growth in Sudan. The importance of this topic comes out from the fact that the urbanization phenomenon is a dynamic phenomenon which leads to structural change in the society; this change is accompanied by a functional change in the different social and economic systems. The study concluded that Sudan, like any other third world countries, is accelerating the urban growth, and its most important characteristics are that it is unbalanced, and there is a large disparity in the amount of salaries between the Nile axis, and the railway axis (the middle), and that the congestion of cities in the last two decades has become an obsession for the officials and the residents of that area, therefore this leads to inability to providing services. The most significant recommendations that, the state’s strategy should focus on distribution and improvement of services, especially health and education in all parts of the country, not only in cities but in the countryside first.